Storytelling as a communication tool for health consumers: development of an intervention for parents of children with croup. Stories to communicate health information - Hartling Lisa; Scott Shannon; Pandya Rena; Johnson David; Bishop Ted; Klassen Terry P (BMC, 2010)
Abstract Background Stories may be an effective tool to communicate with and influence patients because of their ability to engage the reader. The objective of this paper is to describe the development of a story-based intervention for delivery of health evidence to parents of children with croup for use in a randomized controlled trial. Methods A creative writer interviewed parents of children with croup presenting to the pediatric emergency department (ED) and drafted stories. We revised the stories based on written participant feedback and edited the stories to incorporate research evidence and health information. An illustrator and graphic designer developed story booklets which were evaluated through focus groups. Results Ten participants provided feedback on the five stories drafted by the creative writer. Participants liked the concept but found the writing overly sophisticated and wanted more character development and more medical/health information. Participants highlighted specific story content that they liked and disliked. The revised stories were evaluated through focus groups involving eight individuals. Feedback was generally positive; one participant questioned the associated costs. Participants liked the graphics and layout; felt that they could identify with the stories; and felt that it was easier to get information compared to a standard medical information sheet. Participants provided feedback on the story content, errors and inconsistencies, and preferences of writing style and booklet format. Feedback on how to package the stories was provided by attendees at a national meeting of pediatric emergency researchers. Conclusions Several challenges arose during the development of the stories including: staying true to the story versus being evidence based; addressing the use of the internet by consumers as a source of health information; balancing the need to be comprehensive and widely applicable while being succinct; considerations such as story length, reading level, narrative mode, representation of different demographics and illness experiences, graphics and layout. The process was greatly informed by feedback from the end-user group. This allowed us to shape our products to ensure accuracy, credibility, and relevance. Our experience is valuable for further work in the area of stories and narratives, as well as more broadly for identifying and developing communication strategies for healthcare consumers.